ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN NGAWI TAHUN ANGGARAN 2014 – 2018 - Yogi Kharisma Finky Rahayu; Aris Eddy Sarwono; Sunarti Sunarti (Universitas Slamet Riyadi, 2020)
The purpose of this study is to analyze the level of independence, effectiveness, efficiency, growth and analyze the financial performance of the Ngawi Regency government when compared to other regencies in East Java Province. This research was conducted at the local government of Ngawi Regency. The type of data used is secondary data. The results of this study address the financial independence ratio of 10.57% included in the very low category with an instructive relationship pattern. The effectiveness ratio of 138.46% is included in the very effective category. The efficiency ratio of 100.00% is included in the less efficient category. The growth ratio of 01.06% falls into the very low category. The overall financial performance of the Ngawi Regency government can be said to be moderate because it is not in the good or bad category when compared to the Regencies and Cities in East Java Province.